2014
DOI: 10.1007/s12282-014-0518-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating 17 breast cancer susceptibility loci in the Nashville breast health study

Abstract: Background Genome-wide association studies (GWAS) have discovered multiple genetic loci associated with breast cancer risk. Investigating these loci would be helpful to evaluate previous findings and identify causal variants for breast cancer. We evaluated index SNPs in17 of these loci in a study of 1,511 cases and 1,454 controls of European descent. Methods We investigated the overall association with breast cancer and among subtypes defined as ER+ (estrogen receptor positive), ER− (estrogen receptor negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…The p53 gene expression of correlates with BC prognosis [ 21 , 22 ]. Previously, the SNP rs704010 in the ZMIZ1 gene was found to correlate with an increased risk of breast cancer (OR = 1.03) and ER+ BC (OR = 1.02) in women with European ancestry [ 23 ]. Turnbull et al also found rs704010 that the minor allele of “A“have significantly association with BC risk (per-allele OR = 1.38 for stage 1; per-allele OR = 1.13 for stage 2; Combined p = 3.7*10-9) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The p53 gene expression of correlates with BC prognosis [ 21 , 22 ]. Previously, the SNP rs704010 in the ZMIZ1 gene was found to correlate with an increased risk of breast cancer (OR = 1.03) and ER+ BC (OR = 1.02) in women with European ancestry [ 23 ]. Turnbull et al also found rs704010 that the minor allele of “A“have significantly association with BC risk (per-allele OR = 1.38 for stage 1; per-allele OR = 1.13 for stage 2; Combined p = 3.7*10-9) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NBHS is a population-based, case-control study of incident breast cancer among 2,726 women, aged 25 to 75 years, who were newly diagnosed with primary breast cancer between 2001 and 2011 [ 18 , 21 ]. Information on demographic, anthropometric, medical, reproductive, and other characteristics was ascertained through telephone interview by trained interviewers using a structured questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…rs4973768 lies in the untranslated region (3’UTR) of the sodium bicarbonate (Na+HCO3-) cotransporter NBCn1 (SLC4A7) [30]. The Nashville Breast Health Study evaluated this SNP in 1511 cases with a mean age of 53.3 years (range 25–75 years) and identified an association with ER-positive breast cancer [31]. Further, a significant association of SNP rs4973768 with increased breast cancer risk was replicated among different ethnicities in mixed age patients [32, 33].…”
Section: Discussionmentioning
confidence: 99%